Clinical utility of the X‐chromosome array1. Issue 1 (3rd December 2012) - Zarate, Yuri A.; Dwivedi, Alka; Bartel, Frank O.; Bellomo, M. Allison; Cathey, Sara S.; Champaigne, Neena L.; Clarkson, L. Kate; DuPont, Barbara R.; Everman, David B.; Geer, Joseph S.; Gordon, Barbara C.; Lichty, Angie W.; et al.
Abstract Previous studies have limited the use of specific X‐chromosome array designed platforms to the evaluation of patients with intellectual disability. In this retrospective analysis, we reviewed the clinical utility of an X‐chromosome array in a variety of scenarios. We divided patients according to the indication for the test into four defined categories: (1) autism spectrum disorders and/or developmental delay and/or intellectual disability (ASDs/DD/ID) with known family history of neurocognitive disorders; (2) ASDs/DD/ID without known family history of neurocognitive disorders; (3) breakpoint definition of an abnormality detected by a different cytogenetic test; and (4) evaluation of suspected or known X‐linked conditions. A total of 59 studies were ordered with 27 copy number variants detected in 25 patients (25/59 = 42%). The findings were deemed pathogenic/likely pathogenic (16/59 = 27%), benign (4/59 = 7%) or uncertain (7/59 = 12%). We place particular emphasis on the utility of this test for the diagnostic evaluation of families affected with X‐linked conditions and how it compares to whole genome arrays in this setting. In conclusion, the X‐chromosome array frequently detects genomic alterations of the X chromosome and it has advantages when evaluating some specific X‐linked conditions. However, careful interpretation and correlation with clinical findings is needed to determine the significance of such changes. When the X‐chromosome array was used to confirm a suspected X‐linked condition, it had a yield of 63% (12/19) and was useful in the evaluation and risk assessment of patients and families. © 2012 Wiley Periodicals, Inc.